Whey or Casein Hydrolysate with Carbohydrate for Metabolism and Performance in Cycling - Oosthuyse, T.; Carstens, M.; Millen, A. M. E. (International Journal of Sports Medicine, 2015)
The protein type most suitable for ingestion during endurance exercise is undefined. This study compared co-ingestion of either 15 g/h whey or casein hydrolysate with 63 g/h fructose: maltodextrin (0.8:1) on exogenous carbohydrate oxidation, exercise metabolism and performance. 2 h postprandial, 8 male cyclists ingested either: carbohydrate-only, carbohydrate-whey hydrolysate, carbohydrate-casein hydrolysate or placebo-water in a crossover, double-blind design during 2 h of exercise at 60%Wmax followed by a 16-km time trial. Data were evaluated by magnitude-based inferential statistics. Exogenous carbohydrate oxidation, measured from 13CO2 breath enrichment, was not substantially influenced by co-ingestion of either protein hydrolysate. However, only co-ingestion of carbohydrate-casein hydrolysate substantially decreased (98% very likely decrease) total carbohydrate oxidation (mean±SD, 242±44; 258±47; 277±33 g for carbohydrate-casein, carbohydrate-whey and carbohydrate-only, respectively) and substantially increased (93% likely increase) total fat oxidation (92±14; 83±27; 73±19 g) compared with carbohydrate-only. Furthermore, only carbohydrate-casein hydrolysate ingestion resulted in a faster time trial (−3.6%; 90% CI: ±3.2%) compared with placebo-water (95% likely benefit). However, neither protein hydrolysate enhanced time trial performance when compared with carbohydrate-only. Under the conditions of this study, ingesting carbohydrate-casein, but not carbohydrate-whey hydrolysate, favourably alters metabolism during prolonged moderate-strenuous cycling without substantially altering cycling performance compared with carbohydrate-only.
Keywords: protein hydrolysate; exogenous carbohydrate oxidation; multiple transportable carbohydrates; endurance exercise; gastrointestinal comfort; cycling time trial